A reverse biomarker-derived maturity trend in Triassic Yanchang Formation shales from the Ordos Basin in China - Xiaoliang Chen; Haiping Huang; Mingming Yan; Bin Zhang; Wei Wang; Zhiguo Mao; Dehao Bai; Dahai Zhao; Qihao Li (Natural Gas Industry B)
Organic-rich shales from the Triassic Yanchang Formation in the Ordos Basin in China are mainly derived from aquatic organisms with type II kerogen. A reverse maturity trend, derived from the commonly used biomarker maturity parameter Ts/(Ts + Tm) occurs in the depth profiles of the Chang 73 submember and the Chang 8 member. In contrast, maturity proxies derived from aromatic compounds show a normal sequence for more deeply buried Chang 8 samples exhibiting higher maturity levels, as expected. To explain the abnormal phenomenon, multiple controlling factors—including the paleoredox condition, water salinity, the clay mineral content and composition, biodegradation, the primary migration fractionation effect, and organofacies—are considered. It was found that organofacies BC (HIo = 400-250) appear in the Chang 8 samples, while organofacies B (HIo = 400-650) appear in the Chang 73 submember. The results suggest that variation in organofacies has a significant impact on Ts/(Ts + Tm) values, even for samples with the same kerogen type and similar source input, and is primarily responsible for the reverse maturity trend in the depth profiles.